Analisis Prediksi Kebangkrutan Pada Perusahaan Sektor Properti dan Real Estate Yang Terdaftar di Indeks Saham Syariah Indonesia (ISSI) - Khoirul Yahya; Hendra Harmain; Atika Atika (Departement of Mathematics Education, 2023)
The goal of this study is to use the Altman Z-Score approach to predict and quantify the level of bankruptcy in Property and Real Estate Sector Firms listed on the Indonesian Sharia Stock Index. Moreover, to determine which businesses have the highest and lowest rates of bankruptcy. A company's financial ratios based on the financial ratios of the Altman Z-Score are the variable utilized in the study's discussion of using the original Altman Z-Score to predict bankruptcy. Working capital to total assets divided (X1), retained earnings to total assets divided (X2), earnings before interest and taxes divided (X3), share market value to total debt divided (X4), and sales to total assets divided (X1) are the financial ratios (X5). This study is quantitative in nature. Secondary data in the form of annual financial reports that were downloaded from www.idnfinancials.com between 2016 and 2019 is the type of data that was used. The Altman Z-Score, which has the formula Z = 1.2.X1 + 1.4.X2 + 3.3.X3 + 0.6.X4 + 1.0.X5, is used in the data analysis to determine the level of bankruptcy for the years 2016 to 2019. The findings of this study show that from 2016 to 2019 APLN, ADHI, ASRI, DILD, GAMA, MDLN, CTRA, and DART are in the danger zone according to the results of the bankruptcy prediction analysis based on the Altman Z-Score. BSDE company is in a vulnerable/grey zone. Meanwhile, the PLIN company is in a safe zone. The company that has the highest bankruptcy rate is DART and the company that has the lowest bankruptcy rate is PLIN.